Prescribing pattern of drugs in chronic kidney disease patients on hemodialysis at a tertiary care hospital - Murthy B. V., Narayana; V., Satyanarayana (International Journal of Basic & Clinical Pharmacology, 2017)
Background: CKD (chronic kidney disease) is a general term for heterogeneous disorders affecting kidney structure and its function. It is defined as either kidney damage or a decreased glomerular filtration rate of less than 60 mL/min/1.73m2 for 3 or more months. Objective of present work is to study the drug utilization pattern in chronic kidney disease patients undergoing hemodialysis. Methods: After taking the clearance and approval from the institutional ethics committee, a cross sectional prospective observational study conducted on chronic kidney disease (CKD) patients undergoing hemodialysis, in the department of nephrology, of Rajarajeshwari Medical College and Hospital, Bangalore. The data was analyzed descriptively. Results: Study included 52 patients, among them 41 males, 11were females, with a mean age of 47.6yrs. In our study large number pt were suffering from hypertension (HTN) 88.46% (46), in them the calcium channel blocker (CCB) 08.48% (38) was most commonly prescribed anti hypertensive drug. Around 1/3 of pt suffering from diabetes mellitus (DM) 36.53% (19) most of these patients were treated with them treated with oral hypoglycemic agents (OHA), and less than half of pt treated with insulin01.56% (07). Other drugs like phosphate binders (calcium carbonate & acetate) used in 11.16% (50), aspirin in 08.70% (39), statins in 10.04% (45) pt were being most commonly prescribed drugs. Totally 448 drugs were prescribed In 52 pts Ie about 8.61 drugs / prescription, showing poly pharmacy. Conclusions: Patients undergoing hemodialysis with CKD will be having multiple diseases associated, regular monitoring and counseling regarding these diseases and its complication may reduce the incidence of CKD and the mortality and morbidity associated. The poly pharmacy noted in the study found inevitable because of the multifactorial etiologiesinvolved and needful multi-interventional approach towards it.